1996
DOI: 10.1097/00000658-199602000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for En Bloc Vein Resection in the Treatment of Pancreatic Adenocarcinoma Adherent to the Superior Mesenteric-Portal Vein Confluence

Abstract: When necessary, segmental resection of the SMPV confluence may be performed safely during pancreaticoduodenectomy for periampullary malignant tumors. Tumors invading the SMPV confluence are not associated with histologic parameters suggesting a poor prognosis. Our data suggest that venous involvement is a function of tumor location rather than an indicator of aggressive tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
209
1
13

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(239 citation statements)
references
References 31 publications
16
209
1
13
Order By: Relevance
“…However, some high-volume centers perform resection and reconstruction of a short segment of the portal vein or superior mesenteric vein (SMV) for limited tumor involvement of the SMV, portal vein, or the confluence [73]. Studies have also shown that tumors with portal vein involvement have similar frequency of positive lymph nodes or aneuploidy compared to those without portal vein involvement [76][77][78]. These findings suggest that venous involvement is a function of tumor location rather than an indicator of aggressive tumor biology.…”
Section: Vascular Resectionmentioning
confidence: 99%
“…However, some high-volume centers perform resection and reconstruction of a short segment of the portal vein or superior mesenteric vein (SMV) for limited tumor involvement of the SMV, portal vein, or the confluence [73]. Studies have also shown that tumors with portal vein involvement have similar frequency of positive lymph nodes or aneuploidy compared to those without portal vein involvement [76][77][78]. These findings suggest that venous involvement is a function of tumor location rather than an indicator of aggressive tumor biology.…”
Section: Vascular Resectionmentioning
confidence: 99%
“…Many studies that have looked at indications for operative exploration and resection in the presence of mesentericoportal axis involvement reported no difference in morbidity, mortality, and survival rates from those patients who underwent standard resection, and outcomes were in fact better than in patients without operative treatment because of venous involvement [20][21][22][23][24]. On the contrary, Worni et al demonstrated an increase in intraoperative and postoperative morbidity but no increase in operative mortality in patients undergoing concomitant vascular resections [25].…”
Section: Venous Involvementmentioning
confidence: 99%
“…Arterial involvement remains a contraindication for resection due to the high morbidity involved and low benefit gained with regards to survival. On the other hand, several reports [8][9][10][11][12][13] showed that resection/reconstruction of the PV or SMPV confluent were safe and improved survival. Therefore, tumors in contact with major venous vasculature without circumferential encasement, PV thrombosis or large involvement of the SMPV confluent must be considered resectable tumors.…”
Section: Resection Ratementioning
confidence: 99%
“…However, patients diagnosed with non-metastatic LAPA with a good clinical status are likely to undergo chemoradiation (CRT) 7 . Although it is impossible for patients with arterial adhesion/invasion to undergo resection, venous involvement proved not to be a contraindication to resection [8][9][10][11][12][13] . Thus, despite low resection rates, several reports showed interesting results on overall survival 14-20 after pancreaticoduodenectomy (PD) for LAPA.…”
Section: Introductionmentioning
confidence: 99%